Producción de biogás a partir de gallinaza con la adición de promotores de fermentación a 3 dosis, cantón Salcedo, provincia de Cotopaxi, periodo 2014 – 2015 - Córdova Cortez, Sofía Priscila (2015)
This research was developed in the San Miguel parish, El Calvario neighborhood, located at 2628 m.a.s.l., with a temperature average of 14.06°C, relative humidity average of 76.2% and a multi-year precipitation of 621.28 mm. The factors studied were: FACTOR (A) Evaluation of two promoters of fermentation (efficient local microorganisms and efficient trading microorganisms) and FACTOR (B) evaluation of three adjustments of C/N ratio (15:1 / 20:1 / 25:1). Evaluated in discontinuous biodigesters type batch, disposed in a randomized complete block design with a 2 X 3 + 1 factorial arrangement; with a variance analysis and Tukey tests at 5% in order to establish statistical significance….